Echinacoside Suppresses Amyloidogenesis and Modulates F-actin Remodeling by Targeting the ER Stress Sensor PERK in a Mouse Model of Alzheimer’s Disease - Dai, Yuan; Han, Guanghui; Xu, Shijun; Yuan, Yongna; Zhao, Chunyan; Ma, Tao (Frontiers in Cell and Developmental Biology, 2020)
Endoplasmic reticulum stress (ERS) plays a vital and pathogenic role in the onset and progression of Alzheimer’s disease (AD). Phosphorylation of PKR-like endoplasmic reticulum kinase (PERK) induced by ERS depresses the interaction between actin-binding protein filamin-A (FLNA) and PERK, which promotes F-actin accumulation and reduces ER-plasma membrane (PM) communication. Echinacoside (ECH), a pharmacologically active component purified from Cistanche tubulosa, exhibits multiple neuroprotective activities, but effects of ECH on ERS and F-actin remodelling remain elusive. Here, we found ECH could inhibit the phosphorylation of PERK. Firstly ECH can promote PERK-FLNA combination and modulate F-actin remodelling. Secondly, ECH dramatically decreased cerebral Aβ production and accumulation by inhibiting the translation of BACE1, and significantly ameliorated memory impairment in 2×Tg-AD mice. Furthermore, ECH exhibited high affinity to either mouse PERK or human PERK. These findings provide novel insights into the neuroprotective actions of ECH against AD, indicating that ECH is a potential therapeutic agent for halting and preventing the progression of AD.